Sistem Pendukung Keputusan Pemilihan Aplikasi Jasa Angkut Barang Menggunakan PIPRECIA-S dan Composite Performance Index - Sinlae, Alfry Aristo Jansen; Jamaludin, Jamaludin; Nugroho, Nurhasan; Badaruddin, Muliati (Forum Kerjasama Pendidikan Tinggi, 2024)
Freight service applications play a crucial role in supporting logistics efficiency and goods mobility. However, with the multitude of available applications, users often face difficulties in determining which application best suits their needs. The manual process of selecting these applications requires users to search and compare information from various sources, which demands considerable time and effort and is prone to subjectivity. This study aims to develop a Decision Support System (DSS) that is quick and accurate in determining the best freight service application using the Simplified Pivot Pairwise Relative Criteria Importance Assessment (PIPRECIA-S) method and the Composite Performance Index (CPI). The PIPRECIA-S method is used to objectively and systematically determine the criteria weights, while the CPI method is employed to identify the best alternative by integrating various performance aspects into a single, easily understood composite measure. In the conducted case study, the best alternative identified was Lalamove (A2), with a composite index score of 122.55, followed by Deliveree (A3) with a score of 114.39, Lion Parcel (A1) with a score of 109.24, GoBox (A4) with a score of 102.04, and The Lorry (A5) with a score of 99.04. The DSS calculations were consistent with the manual calculations, demonstrating its validity and reliability. Usability testing showed an average score of 90%, indicating that the developed DSS possesses the necessary functionality with an intuitive and user-friendly interface.